Early Liver Transplantation for Patients With Acute Alcoholic Hepatitis: Public Views and the Effects on Organ Donation. Issue 6 (23rd February 2015) - Stroh, G.; Rosell, T.; Dong, F.; Forster, J.
<x xml:space="preserve">Abstract</x> Patients with severe acute alcoholic hepatitis may not survive to fulfill the standard 6 months of abstinence and counseling prior to transplantation. A prospective study demonstrated that early liver transplantation in such patients improved 2 year survival from 23% to 71% and only 3 of 26 patients returned to drinking after 1140 days; graft function was unaffected. Nonetheless, this treatment protocol may raise public concerns and affect organ donation rates. A total of 503 participants took a survey made available at an online crowdsourcing marketplace. The survey measured attitudes on liver transplantation generally and early transplantation for this patient population, in addition to measuring responses to nine vignettes describing fictional candidates. The majority of respondents (81.5%, n = 410) was at least neutral toward early transplantation for these patients; only a minority (26.3%) indicated that transplantation in any vignette would make them hesitant to donate their organs. Middle‐aged patients with good social support and financial stability were viewed most favorably (p < 0.001). Age was considered the most important selection factor and financial stability the least important factor (each p < 0.001). Results indicate early transplantation for carefully selected patients with acute alcoholic hepatitis may not be as controversial to the public as previously thought.